Uma nova proposta para o treinamento do arremesso de lance livre no basquetebol - Cedra, Cristiano (2007)
The free throw is a kind of basketball shot and it occurs as a result of breaking some of the rules of the game. Approximately 25% of all points earned in a basketball game come from free throws. In basketball teaching or practicing, free throws are usually the first kind of shot taught, forming the basis for more advanced shooting techniques. Despite its importance, average free throw accuracy has been below 70%; only a few players have managed to achieve a higher average. In this paper a new method of free throw training is presented by progressive and gradual techniques aimed towards specifications changes in materials used in training (in this case, the diameter of the basketball rim and its height). Starting from basic conditions (larger diameters and lower baskets) to those seen as more complex (basketball s official specifications), trying to reach gradually the average accuracy in professional basketball free throwing. In this research, 12 athletes aged from 13 to 14 years old were chosen from a competitive basketball team to participate in it. Then, they were submitted to two stages at the baseline condition. In the first stage, 39 sessions of 10 free throws were shot in each session. In the second stage, the athletes had 13 sessions of 30 shots in each session, out of which 10 were shot from the official free throw line, 10 from an intermediate distance between the free throw line and the basket and the last 10 were shot very close to the basket. After this stage, the athletes were divided into two groups: group 1 was submitted to an intervention related to the diameter of the basket and group 2, to an intervention related to the height of the basket. The fading procedure was identical for both groups that went through the multielement baseline design. Each athlete went through 9 fading practice stages, and, in every stage, should score at least 70% of the free throws to go on to the next stage. Stage 1 was carried out using a closer distance to the basket and a larger diameter (group 1) or a lower height (group 2). Progressively, the distance was increased, passing through the intermediate distance until reaching the official free throw distance, keeping to the same diameter and height specifications. When the athlete reached the official distance, he would go back to the starting line and resume his shooting but now the diameter and height would be set to the intermediate specifications. Gradually, the athlete should reach the official distance and specifications of basketball. The next stage was identical to the baseline condition and had the purpose of evaluating whether the results achieved in the last modified stage would last once the treatment was removed. Analyzing the results, it is made clear that practicing shots through repetition did not produce the results expected in the selected group, at best, it only established their previous marks. Being exposed to different distances without using progression through fading also did not bring improvements to the performance of the athletes and the level of accuracy in the closest distance was higher than in the intermediate distance, which was also higher than in the official distance suggesting that distance is a decisive factor when evaluating basketball shots. While group 1 achieved an overall improvement throughout the practice, some of the athletes in group 2 actually showed a loss in performance, suggesting that the diameter of the rim is, in fact, a more critical factor than the height of the basket. The fading procedure has brought improvements to the level of accuracy of the evaluated athlet